ANAESTHETIC MANAGEMENT OF MASS CASUALTIES-WHAT SHOULD BE THE DRUG OF CHOICE? Mass Casualties - Ashraf, Mohammad; Sheikh, Irfan Ali; Waleem, Sheikh Saadat Ullah (Pakistan Armed Forces Medical Journal, 2006)
Background: Based on the experience of earthquake 8th October 2005 choice of best anaesthetic management for mass casualties was determined. Patients were subjected to all types of anaesthesia and then best out of these came out to be ketamine. Duration of the Study: One month. Patients and Methods: A total of 180 patients were anaesthetized by different methods during one month after earthquake. Results: Out of 120 patients 80 received general, 74 ketamine, 22 spinal and 4 regional anaesthesia. 41% who received ketamine anaesthesia showed uneventful recovery without any complication. Conclusion: It is concluded that ketamine alone can be used very safely in case of mass casualties as also recommended in literature.